THE USE OF THE SPOTIFY APPLICATION TO IMPROVE STUDENTS’ EXTENSIVE LISTENING SKILLS - Azis, Nurul Maghfirah; Jabu, Baso; Muhayyang, Maemuna (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This research aims to evaluate the effectiveness of the Spotify application as a medium for learning English, particularly in enhancing students' extensive listening skills and their interest in using the app. The research employed a pre-experimental quantitative method and involved a sample of 25 students from Class XI 3 at MAN 1 Kendari, selected through cluster random sampling. Data were collected using tests and questionnaires. The data indicate a noteworthy improvement in students' extensive listening skills with the use of Spotify. The average score increased from 55.40 before the intervention (pre-test) to 90.80 after the intervention (post-test). The t-test results showed a significant difference with a Sig. (2-tailed) value of 0.000, which is less than 0.05. This supports the research hypothesis (H1 accepted, H0 rejected), indicating that Spotify effectively improves the extensive listening skills of Class XI 3 MAN 1 Kendari students. Additionally, the questionnaire results showed that the majority of students had a positive attitude towards using the Spotify application for learning. Based on these findings, The Spotify application is an advantageous tool for improving students' listening skills and is widely accepted as an educational resource.